Normal Pressure Hydrocephalus in the Elderly: A Narrative Review of Diagnostic Complexity, Biomarker Potential, and Surgical Outcomes - Shah, Ali Qudratullah; Shah, Rukan Aalamuddin; Khatoon, Erum; Ramzan, Anam; Chawhan, Muhammad Bilawal; Lund, Aakash; Kalhoro, Muneeb Rehman; Solangi, Jawad Rehman; Soomro, Abdul Wasay; Shaikh, Iftikhar Ahmed (Biological and Clinical Sciences Research Journal, 2025)
Normal pressure hydrocephalus (NPH) is a reversible cause of dementia in older adults, characterized by the clinical triad of gait disturbance, cognitive decline, and urinary incontinence. Owing to overlapping symptoms and low cerebrospinal fluid (CSF) Aβ42 levels, NPH is frequently misdiagnosed as Alzheimer’s or Parkinson’s disease. Objective: To provide a comprehensive narrative review of the pathophysiology, diagnostic challenges, treatment options, and prognostic markers of NPH, with a particular focus on implications for low- and middle-income countries (LMICs). Methods: Relevant literature published between 2000 and 2025 was retrieved from PubMed, Scopus, and Google Scholar using the keywords "normal pressure hydrocephalus," "cerebrospinal fluid dynamics," "ventriculoperitoneal shunting," and "biomarkers." Both clinical and experimental studies addressing NPH’s pathophysiology, diagnostic modalities, and treatment outcomes were reviewed, with emphasis on studies applicable to LMIC contexts such as Pakistan. Results: Evidence indicates that disrupted CSF circulation and ventriculomegaly underlie NPH, with diffusion tensor imaging and arterial spin-labelling MRI offering diagnostic refinement. However, limited access to advanced neuroimaging and cultural perceptions of symptoms as "normal aging" contribute to underdiagnosis in LMICs. Ventriculoperitoneal shunting, particularly with fixed-pressure devices, consistently improves gait performance, while cognitive and urinary outcomes are variable. Post-shunt changes in CSF biomarkers (Aβ42, tau) and serum markers (BDNF, TRPV4) demonstrate potential prognostic value. Functional imaging further correlates reduced cerebral blood flow with symptom severity. Conclusion: NPH remains an under-recognized yet treatable neurological disorder. Increasing awareness, developing simplified diagnostic approaches, and ensuring cost-effective treatment strategies are essential to optimizing patient outcomes, particularly in resource-constrained settings.